2007
DOI: 10.1139/f07-117
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between smolt gill Na+, K+ ATPase activity and migration timing to avian predation risk of steelhead trout (Oncorhynchus mykiss) in a large estuary

Abstract: We examined avian predation risk of juvenile steelhead trout (Oncorhynchus mykiss) migrating through the Columbia River Estuary in relation to their osmoregulatory physiology, body length, rearing conditions (hatchery or wild), migration timing, and migration year. From 2003 to 2006, mean gill Na+, K+ ATPase activity of migrating wild steelhead was greater than hatchery steelhead. Hatchery steelhead were always longer than wild steelhead. Wild steelhead never had higher plasma [Na+] or osmolality levels than h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 39 publications
3
45
1
Order By: Relevance
“…These results corroborate previous work suggesting that the susceptibility of Chinook salmon O. tshawytscha smolts to predation by Caspian terns in the Columbia River estuary was influenced by the incidence of disease in the out-migrating smolts (Schreck et al 2006). Kennedy et al (2007) found similar relationships between decreased saltwater preparedness and increased susceptibility of juvenile steelhead to avian predation in the Columbia River estuary, thus supporting the hypothesis that salmonid susceptibility to avian predation is associated with individual fish characteristics and condition.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results corroborate previous work suggesting that the susceptibility of Chinook salmon O. tshawytscha smolts to predation by Caspian terns in the Columbia River estuary was influenced by the incidence of disease in the out-migrating smolts (Schreck et al 2006). Kennedy et al (2007) found similar relationships between decreased saltwater preparedness and increased susceptibility of juvenile steelhead to avian predation in the Columbia River estuary, thus supporting the hypothesis that salmonid susceptibility to avian predation is associated with individual fish characteristics and condition.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies in the Columbia River estuary have noted that hatchery-reared salmonids were more susceptible to avian predation than their wild counterparts (Collis et al 2001;Ryan et al 2003;Kennedy et al 2007). Our results indicate that hatchery-reared steelhead were more susceptible to some avian predators in freshwater systems: double-crested cormorants disproportionately consumed hatchery-reared steelhead relative to wild-origin steelhead, but this was not the case for Caspian terns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that post-smolts are exposed to high predation immediately after sea entry (Reitan et al 1987;Hvidsten and Lund 1988;Dieperink et al 2002) and that the risk of predation increases if fish suffers from osmotic stress (Järvi 1989;Handeland et al 1996;Kennedy et al 2007). It may therefore be suggested that the extended residency of the first smolt group in the lower part of the river was related to their low gill Na + , K + -ATPase activity and a need to improve seawater tolerance before entering seawater.…”
mentioning
confidence: 99%
“…Samples from smolts produced in brood year 2002 were degraded and were not considered in the analyses. We sampled wild smolts using either a screw trap operated at the mouth of Abernathy Creek or from archived tissues collected during annual electrofishing surveys from individuals later determined to have emigrated as smolts (Kennedy et al 2007) from the creek via a PIT tag reader near the mouth of the creek. Collection efforts at the screw trap took place between March and June each year to capture the distribution of emigration timing.…”
Section: Medianmentioning
confidence: 99%